2018
DOI: 10.1038/s41598-018-34305-x
|View full text |Cite
|
Sign up to set email alerts
|

A reduced M1-like/M2-like ratio of macrophages in healthy adipose tissue expansion during SGLT2 inhibition

Abstract: The adipose tissue includes various stromal cells, such as preadipocytes, endothelial cells, fibroblasts, and immune cells, which are involved in adipose tissue functions. We previously reported that, in obese mice, the sodium–glucose cotransporter 2 inhibitor ipragliflozin (Ipra) promoted the expansion of the epididymal adipose tissue (Epi) with increase of serum ketone body concentration. The Ipra-induced adipose tissue expansion did not deteriorate adipose inflammation, or systemic glucose/lipid metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The present study demonstrated that Ipra increased adipocyte size in abdominal PVAT in WD-induced obese and diabetic mice, which is consistent with our previous observation in Epi of diet-induced obese mice treated with SGLT2 inhibitors [19, 31, 32]. The adipocyte hypertrophy in abdominal PVAT accompanied a decrease of inflammation and fibrosis, which corresponded to “healthy adipose expansion” [33].…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrated that Ipra increased adipocyte size in abdominal PVAT in WD-induced obese and diabetic mice, which is consistent with our previous observation in Epi of diet-induced obese mice treated with SGLT2 inhibitors [19, 31, 32]. The adipocyte hypertrophy in abdominal PVAT accompanied a decrease of inflammation and fibrosis, which corresponded to “healthy adipose expansion” [33].…”
Section: Discussionsupporting
confidence: 91%
“…Unlike in vitro conditions, macrophages usually develop mixed phenotypes in vivo in response to disease conditions, and they are difficult to separate using classical M1 or M2 surface markers. For example, it has been reported that macrophage populations display a mixed M1/M2 phenotype in obese patients 21 . The dynamic balance between M1-like and M2-like macrophages tightly controls the disease outcomes, suggesting that regulation of macrophage phenotype is a promising strategy for disease treatment.…”
Section: Macrophage Polarization and Functionsmentioning
confidence: 99%
“…For example, R-BHB, when given to isolated macrophages challenged with Streptococcus uberis , was shown to increase the expression of IL-1 β and IL-10 and the chemokines CXCL2 and CCL5 but had no effect on the expression of TNF- α and TGF- β [ 207 ]. In another report using isolated M1 peritoneal macrophages, R-BHB was shown to decrease the expression of IL-15, but not IL-1 β , TNF- α , or IL-6 [ 208 ]. In calf hepatocytes, R-BHB was shown to increase NF- κ B activity and the expression of IL-1 β , TNF- α , and IL-6 [ 209 ], while ketosis had similar effects in the liver of cows [ 210 ].…”
Section: Molecular Mechanisms Through Which R-bhb Inhibits Inflammmentioning
confidence: 99%